Exploring the Relationship between Perceived Interpersonal Treatment and Organizational Commitment of Health Workers in Selected Health Institutions in Uyo - Ijeoma, Nkeiru; Otu, O. Essien (Practicum Psychologia, 2024)
This study explores the relationship between interpersonal treatment and organizational commitment among Health Workers in Uyo. The participants in the study comprised 105 employees drawn from selected health institutions within Uyo in Akwa Ibom State. They included 75(71.4%) males and 30(28.6%) females. Their ages ranged between 30-50 years, with mean age of 40.04 (SD, 4.70). The study utilized random sampling and purposive sampling techniques to select the organizations and participants respectively. Two measurements were used: perception of fair interpersonal treatment scale and organizational commitment multidimensional scale. The study adopted a correlational design and Pearson Moment Correlational Coefficient served as appropriate statistics for analyses of the data. The study results showed a significant positive relationship between interpersonal treatment and organizational commitment, (r=0.69, p<0.01). This study findings will guide the managers and co-workers of health workers to develop positive and healthy relational climate in workplace to promote and maintain good organizational commitment.